Analisis Pola Asuh Orang Tua pada Motivasi Belajar Siswa Kelas III SD Negeri 1 Pelemkerep - Rohmaniyah, Nur Alfiyatur; Khamdun, Khamdun; Widianto, Eko (EduBasic Journal: Jurnal Pendidikan Dasar, 2020)
Student motivation mostly relies on the parenting style threaten by parents since parenting is a control in providing a positive influence on children. In providing better learning circumstance and motivation, the role of parents is very important because it is used as a reference by children to achieve their learning achievements. This study discussed parenting styles and their implications toward learning motivation of students of elementary school. It also try to find out what the most the influential type of parenting style in associated with learning motivation. This research used descriptive qualitative methods. This research was conducted in State Elementary School 1 of Pelemkerep Mayong Jepara. Students, parents and teachers were involved as the research subjects. This study uses data collection techniques that include observation, interview and documentation. The data analysis used was descriptive qualitative data analysis. There are four types of parenting found, namely permissive, democratic, authoritative, and neglected. The results obtained explained that the democratic parenting style becomes the most efficient parenting style than other types of parenting in order to support learning motivation. A total of 21 respondents used democratic parenting style as a pattern of parenting and influenced elementary school students' learning motivation. Positive parenting would encourage high motivation in learning for student.Â